2023
DOI: 10.1186/s12889-023-15255-0
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ preferences on organisational aspects of psychotherapeutic consultation at work by occupational area, company size, requirement levels and supervisor function – a cross-sectional study in Germany

Abstract: Background Common mental disorders affect a significant proportion of the population worldwide at any given time. Psychotherapeutic consultation at work offers employees with mental distress short-term and low-threshold access to psychotherapeutic treatment. However, this offer is only accepted by one to two percent of the employees to whom it is offered. Taking into account employees ‘ preferences regarding organisational aspects might increase the use of psychotherapeutic consultation at work… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 59 publications
(93 reference statements)
1
10
0
3
Order By: Relevance
“…This is supported by a previous study which found that the intention to seek PT-A was lower for private burden than for occupational burden [16]. Additionally, another previous publication with the same study sample as the present study found that employees of larger companies would be more likely to talk about private burden than employees of middle-sized companies [34]. One possible explanation was that greater anonymity might be guaranteed in larger companies [34].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This is supported by a previous study which found that the intention to seek PT-A was lower for private burden than for occupational burden [16]. Additionally, another previous publication with the same study sample as the present study found that employees of larger companies would be more likely to talk about private burden than employees of middle-sized companies [34]. One possible explanation was that greater anonymity might be guaranteed in larger companies [34].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, another previous publication with the same study sample as the present study found that employees of larger companies would be more likely to talk about private burden than employees of middle-sized companies [34]. One possible explanation was that greater anonymity might be guaranteed in larger companies [34]. Another possible explanation might be that participants may expect different consequences when talking about occupational burden compared to private burden during the consultation.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations